Assessing the emotional impact of colour and music in an online environment. - Chin, Siow Wei. (2008)
The purpose of this reserach is to study the impact of music and colour on consumers' emotional responses in an online environment. Specifically,this research aims to find out how consumers' emotional states may be influenced when they surf Web sites that are different in colours and play music of different tempi.